A novel soft gripper for baby broccoli robotic harvesting - Rizan Mohamed; Gayan Kahandawa Appuhamillage; Joarder Kamruzzaman; Alexandra Keith; Linh Nguyen (Smart Agricultural Technology)
The agricultural industry faces critical challenges such as labor shortages and the growing need for efficient, sustainable harvesting solutions. This paper introduces a novel soft robotic gripper system with real-time force feedback, specifically developed for the autonomous harvesting of baby broccoli, a delicate and labor-intensive crop. The system features a flexible gripper fabricated from thermoplastic polyurethane (TPU), which provides the necessary compliance and durability for handling delicate plant stems. Integrated pressure sensing allows the gripper to dynamically adjust grip forces, maintaining an optimal range to prevent damage to the fragile stems while ensuring secure handling during the cutting process. Our approach combines mechanical design optimization with adaptive force control algorithms to address the variability inherent in agricultural environments. The paper presents the design methodology, system architecture, and experimental validation through field trials that assess gripping reliability, harvesting speed, and crop damage rates. This solution showcases the potential for integrating soft robotics and force feedback to automate the harvesting of delicate crops, reducing labor dependency while preserving crop quality.